Hand av sol : den taktila förnimmelsens funktioner i jagets relation till Gud i Solveig von Schoultz lyrik - Envall, Carola (Åbo Akademis förlag, 2021)
Abstract: Solar hand : Tactile Perception in the Relationship between the Self and God in the Poetry of Solveig von Schoultz.
Keywords: Schoultz, Solveig von, : 1907-1996; teologia; kirjallisuudentutkimus; lyriikka; mielteet; ruumiillisuus; kosketus; minä; Jumala; teologi; litteraturvetenskap; lyrik; förnimmelser; kroppslighet; beröring; jaget; Gud